PENGEMBANGAN INSTRUMEN EVALUASI FORMATIF PEMBELAJARAN PAI BERBASIS QUIZIZ UNTUK MENDUKUNG MOTIVASI BELAJAR SISWA DI MI AL-ISHLAH PALEMBANG - Albab Mananna; Asiana; Dina Bahriani Putri; Donna Takrim; Sri Juwita; Dian Erlina; Muhammad Isnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a Quizizz-based formative assessment instrument for Islamic Religious Education (PAI) on the topic of belief in qada and qadar for Grade VI students at MI Al-Ishlah Palembang. The study used a Research and Development (R&D) approach adapted from the Borg and Gall model, including research, planning, product development, validation, and limited field testing. Data were collected through observation, documentation, questionnaires, and student trials. Validation results showed high feasibility, with scores of 85% from media experts, 85% from evaluation experts, and 96% from subject matter experts. A trial involving 12 students indicated that most students had moderate (50%) and high (33%) learning motivation. These findings suggest that the Quizizz-based formative assessment instrument is valid, feasible, and effective in supporting students’ learning motivation in PAI learning.